A családbarát foglalkoztatás néhány jellemzője a hazai szervezetekben - Bencsik, Andrea; Juhász, Tímea (Jelenkori Társadalmi és Gazdasági Folyamatok, 2010)
Several theories were born connecting with the motivation, and these theories are the principles of strategies used by leaders successfully. These theories principally focus on the reasons and processes which determine a person’s behaviour. Nowadays, the former traditional elements of motivation like the salary, the state, the content of work, the safety of job, etc, are completed with new elements and contents. So, for example, family commitment and improving the ability of employees are also becom-ing important elements. The question and treatment of the reconciliation of work and fam-ily demand more and more attention to this problem from different organizations. We were curious how the Hungarian organizations treated the problem, which is why we have conducted an empirical research of this question. In our publication, we would like to present some results of this survey together with the confirmation of our hypothesis.